Sacred Strategies Transforming Synagogues from Functional to Visionary. - Aron, Isa.; Cohen, Steven M.; Hoffman, Lawrence A.; Kelman, Ari Y. (Lanham : Rowman & Littlefield Publishers, 2010)
Sacred Strategies is about eight synagogues that reached out and helped people connect to Jewish life in a new way--congregations that had gone from commonplace to extraordinary. Over a period of two years, researchers Aron, Cohen, Hoffman, and Kelman interviewed 175 synagogue leaders and a selection of congregants (ranging from intensely committed to largely inactive). They found these congregations shared six traits: sacred purpose, holistic ethos, participatory culture, meaningful engagement, innovation disposition, and reflective leadership and governance. They write for synagogue leaders.
Acknowledgments; Chapter 2. A Portrait of "Visionary": The Characteristics We Saw; Chapter 4. Visionary Learning: Schooling for Everyone; Chapter 6. Transformation in Practice: Moving toward Change; Appendix B: Interview Protocol; 1; 2; 3; 5; 6; 7; 8; 9; 10; 11; 12; 13; 14; 15; 16; 17; 18; 19; 20; 21; 22; 23; 24; 25; 26; 27; 28; 4
Description based upon print version of record.
Keywords: Synagogues -- United States -- History -- 21st century; Jewish leadership -- United States -- History -- 21st century; Judaism -- United States -- History -- 21st century; RELIGION / Judaism / General; Electronic books